ISLAM RAHMATAN LIL ‘ALAMIN DALAM PEMIKIRAN BUYA YAHYA:ANTARA TRADISI DAN MODERNITAS - Alifahtul Zahro; Elsha Nur Hikmah, Mufid Irsyad, Abdul Fadhil (Adisam Publisher, 2025)
This research examines Buya Yahya's thoughts on the Islamic concept of Rahmatan lil 'Alamin in the context of tradition and modernity. As a cleric who is active in da'wah, Buya Yahya is known for being able to combine traditional Islamic values with the modern challenges faced by the people today. This research uses a descriptive qualitative approach with the library research method to analyze Buya Yahya's works, whether in the form of lectures, books, or preaching recordings. Apart from that, content analysis techniques and a hermeneutic approach were applied to explore the meaning and relevance of his thoughts. The research results show that Buya Yahya's thoughts on Islam Rahmatan lil 'Alamin emphasize the importance of moderation, tolerance, and social concern. Within the framework of tradition, he emphasized the values of noble morals and exemplary behavior inherited by Salaf scholars. Meanwhile, in facing modernity, Buya Yahya stressed the importance of openness to technology and global culture, as long as it does not conflict with Islamic principles. This research concludes that Buya Yahya's preaching succeeded in bridging the strong Islamic tradition with the dynamics of modernity, making it relevant in responding to the challenges of the times.